High-flux laser transfer printing method for solid film
By using two lasers of different peak power densities in the laser transfer method to irradiate the solid film within the preset time interval, the problem of insufficient film thickness in the traditional method is solved, and the effect of high-throughput transfer and reduced manufacturing cost is achieved. .
Patent Information
- Application Number
- CN202411753735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Traditional laser transfer methods use thin solid-state donor films, which leads to high manufacturing difficulty and cost and low transfer efficiency, limiting its application scenarios.
Two transfer lasers with different peak power densities are used to irradiate the solid films separately within the preset time interval, and a high-throughput transfer process is achieved using thermal diffusion and surface pushing effects.
High-throughput transfer of solid-state films is realized, reducing manufacturing difficulty and cost, and ensuring transfer quality and stability.
Smart Images

Figure CN119427983A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser transfer, and in particular to a high-throughput laser transfer method for a solid film. Background Art
[0002] Laser transfer technology is a manufacturing method based on the principle of laser-induced forward transfer. It uses pulsed laser to irradiate thin film materials attached to a transparent substrate to achieve local transfer of thin film materials, and form point, two-dimensional or three-dimensional structures by point-by-point accumulation. The above-mentioned thin film material is also called a donor, and both liquid slurry thin layers and solid films can be used as donors. When a solid film is used as a donor, the donor has higher consistency and there is no instability and contamination caused by the fluid. Therefore, it can not only achieve high-precision transfer, but also facilitate the storage of the donor and its wide application in various complex sites.
[0003] However, when using a solid film as a donor, the donor thickness reported in the reports is generally only in the nanometer or submicron order. For example, the Chinese invention patent "Method and Apparatus for Repairing Printed Circuit Traces" with publication number CN104797087A discloses that the donor film thickness is related to the laser pulse width, and the donor film thickness is ≤1μm. This is because the traditional laser transfer method generally uses a single short-pulse laser to irradiate the donor, resulting in competition between the thermal diffusion and surface push effect after the laser action, while the peak power density of ordinary short-pulse lasers is high and the surface push effect is strong, making it difficult for the laser to effectively diffuse the thermal effect on the donor, and the film will tear. Therefore, the traditional laser transfer method must use a thin donor film.
[0004] Furthermore, since the solid donor film used in the prior art is relatively thin, on the one hand, its manufacturing difficulty and cost are increased, and on the other hand, the efficiency of the laser transfer process is reduced, limiting its application scenarios. Therefore, how to reduce the manufacturing difficulty and cost of the solid donor film while achieving fast and stable material transfer is one of the major challenges facing this technology. Summary of the invention
[0005] The purpose of the present invention is to propose a high-throughput laser transfer method for solid-state films, which is conducive to achieving high-throughput transfer of solid-state films, reducing the manufacturing difficulty and cost of solid-state donor films while achieving rapid and stable material transfer, so as to overcome the shortcomings of the prior art.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] A high-throughput laser transfer method for solid-state thin films comprises the following steps:
[0008] A. preparing a transfer film, wherein the transfer film comprises a transparent substrate and a solid film, wherein the solid film is attached to the inner surface of the transparent substrate;
[0009] B. applying a first transfer laser to the transfer film, allowing the first transfer laser to sequentially pass through the outer surface and the inner surface of the transparent substrate and irradiate the solid film to form a melted area;
[0010] C. After a preset time interval, a second transfer laser is applied to the transfer film, so that the second transfer laser sequentially passes through the outer surface and the inner surface of the transparent substrate and irradiates the melted area of the solid film;
[0011] In step B, the peak power density of the first transfer laser when it reaches the solid film is ≤50MW / cm 2 ;
[0012] In step C, the peak power density of the second transfer laser when it reaches the solid film is ≥100MW / cm 2 .
[0013] Preferably, in step C, the preset time interval is a, in units of s, and a satisfies:
[0014] 0.1*(b 2 / c)≤a≤10*(b 2 / c);
[0015] Wherein, b is the thickness of the solid film, in m; c is the thermal diffusivity of the material of the solid film, in m 2 / s.
[0016] Preferably, in step B, the first transfer laser is a continuous laser.
[0017] Preferably, in step B, the first transfer laser is a pulse laser, and the pulse width of the first transfer laser is ≥1 μs.
[0018] Preferably, in step C, the second transfer laser is a pulse laser, and the pulse width of the second transfer laser is 0.1-100 ns.
[0019] Preferably, the thickness of the solid film is ≥5 μm.
[0020] The technical solution provided by the present invention may include the following beneficial effects:
[0021] 1. This scheme first uses a first transfer laser with a lower peak power density to irradiate the solid film, so that the solid film after the laser action mainly undergoes a thermal diffusion effect, thereby causing the irradiated area of the solid film to melt and form a melted area. When the irradiated area of the solid film melts to a certain extent, that is, after a preset time interval in this case, the second transfer laser with a higher peak power density is used to irradiate the melted area of the solid film, so that the power input is concentrated, so that the melted area of the solid film after the laser action mainly undergoes a surface push effect, which pushes the partially or completely melted film material in the melted area to vaporize and transfer, thereby achieving a stable and high-throughput transfer effect.
[0022] 2. Since this solution uses two transfer lasers with different peak power densities to irradiate the solid film separately within a preset time interval, a high-throughput transfer process of the solid film can be achieved. Therefore, when the above-mentioned high-energy laser transfer method is applied to a thick solid film, the stable transfer of the solid film can be ensured while ensuring the transfer quality. Furthermore, due to the effective use of thick solid films, the manufacturing difficulty and cost of the existing technology due to the use of a thin solid donor film can be reduced, which greatly solves the shortcomings of the existing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic flow diagram of a high-throughput laser transfer method for a solid-state film according to the present invention.
[0024] Figure 2 It is a schematic diagram of the solid-liquid region evolution of the solid film in Example 1 of the present invention.
[0025] Figure 3 Schematic diagram of the evolution of the maximum temperature in the solid film over time in Example 1 of the present invention.
[0026] Figure 4 Schematic diagram of the evolution of the maximum temperature in the solid film over time in Example 2 of the present invention.
[0027] Figure 5 It is a schematic diagram of the solid-liquid region evolution of the solid film in Example 3 of the present invention.
[0028] Figure 6 Schematic diagram of the evolution of the maximum temperature in the solid film over time in Example 3 of the present invention. DETAILED DESCRIPTION
[0029] A high-throughput laser transfer method for solid-state thin films comprises the following steps:
[0030] A. preparing a transfer film, wherein the transfer film comprises a transparent substrate and a solid film, wherein the solid film is attached to the inner surface of the transparent substrate;
[0031] B. applying a first transfer laser to the transfer film, allowing the first transfer laser to sequentially pass through the outer surface and the inner surface of the transparent substrate and irradiate the solid film to form a melted area;
[0032] C. After a preset time interval, a second transfer laser is applied to the transfer film, so that the second transfer laser sequentially passes through the outer surface and the inner surface of the transparent substrate and irradiates the melted area of the solid film;
[0033] In step B, the peak power density of the first transfer laser when it reaches the solid film is ≤50MW / cm 2 ;
[0034] In step C, the peak power density of the second transfer laser when it reaches the solid film is ≥100MW / cm 2 .
[0035] Since traditional laser transfer methods generally use a single short-pulse laser to irradiate the donor, the thermal diffusion and surface push effect after the laser action compete with each other. The peak power density of ordinary short-pulse lasers is high and the surface push effect is strong, making it difficult for the laser's thermal effect on the donor to be effectively diffused, and the film will tear.
[0036] Therefore, in order to effectively utilize the thermal diffusion and surface pushing effects after the laser acts on the solid film, the laser transfer method of this scheme uses two transfer lasers with different peak power densities to irradiate the solid film separately within a preset time interval, so that the solid film undergoes changes mainly based on the preset effect, thereby realizing a high-throughput transfer process.
[0037] Specifically, this solution first uses a first transfer laser with a lower peak power density to irradiate the solid film, so that the solid film after the laser action mainly undergoes a thermal diffusion effect (at this time, the surface push effect is not strong), thereby causing the irradiated area of the solid film to melt and form a melted area. When the irradiated area of the solid film melts to a certain extent, that is, after a preset time interval in this case, the second transfer laser with a higher peak power density is used to irradiate the melted area of the solid film, so that the power input is concentrated, so that the melted area of the solid film after the laser action mainly undergoes a surface push effect (at this time, the thermal diffusion effect is not strong), and the film material in the partially or completely melted melted area is pushed to vaporize and transfer, thereby achieving a stable and high-throughput transfer effect.
[0038] Further, in step C, the preset time interval is a, the unit is s, and a satisfies:
[0039] 0.1*(b 2 / c)≤a≤10*(b 2 / c);
[0040] Wherein, b is the thickness of the solid film, in m; c is the thermal diffusivity of the material of the solid film, in m 2 / s.
[0041] In addition, in order to take into account both the effective melting and stability of the melting area, the present solution also optimizes the preset time interval a so that it satisfies the above formula, which can effectively ensure that the irradiated area of the solid film after the first transfer laser irradiation is in a melted state. If the preset time interval between the irradiation of the first transfer laser and the second transfer laser is too short, it is easy to cause the melting depth of the solid film to be shallow, and even under the action of the second transfer laser, it is not easy to stably detach from the inner surface of the transparent substrate; if the preset time interval between the irradiation of the first transfer laser and the second transfer laser is too long, the irradiated area of the solid film will be in a liquid state for a long time, which is easy to cause the instability of the molten pool and affect the transfer quality.
[0042] To further illustrate, in step B, the first transfer laser is a continuous laser.
[0043] In a preferred embodiment of the present technical solution, the first transfer laser used in the present solution is a continuous laser. Since the peak power density of the continuous laser is related to the average power of the laser and the laser spot size, the peak power density can be adjusted to meet the transfer requirements of the present solution by adjusting the above parameters.
[0044] To further illustrate, in step B, the first transfer laser is a pulse laser, and the pulse width of the first transfer laser is ≥1 μs.
[0045] In another preferred embodiment of the present technical solution, the first transfer laser used in the present solution is a pulse laser with a pulse width ≥ 1μs. In pulse lasers with the same peak power density, the shorter the pulse width, the faster the heat input rate. Therefore, when the pulse width of the first transfer laser is too short, the temperature inside the solid film may rise sharply, breaking through the vaporization temperature in a short time, generating a violent surface driving force, and because the action time during the laser transfer process is generally short, it is easy to cause insufficient heat diffusion inside the solid film, and it is difficult to ensure that after the first transfer laser irradiates the solid film, the solid film mainly undergoes a heat diffusion effect.
[0046] In addition, since the peak power density of the pulsed laser is also related to the single pulse energy of the laser and the laser spot size, the peak power density can be adjusted to meet the transfer requirements of this solution by adjusting the above parameters.
[0047] To further illustrate, in step C, the second transfer laser is a pulse laser, and the pulse width of the second transfer laser is 0.1-100 ns.
[0048] Similarly, in a pulsed laser with the same peak power density, the shorter the pulse width, the faster the heat input rate. Since this solution requires that after the second transfer laser irradiates the melted area of the solid film, a change mainly caused by the surface push effect occurs, the pulse width of the second transfer laser is preferably 0.1 to 100ns. If a laser with a longer pulse width is used at this time, the surface push effect will not be obvious, making it difficult to transfer the melted area; if a laser with a shorter pulse width is used at this time, the surface push effect will be too obvious, which will easily lead to the fragmentation of the melted area.
[0049] It is further specified that the thickness of the solid film is ≥5 μm.
[0050] Since the present solution utilizes two transfer lasers with different peak power densities to irradiate the solid film separately within a preset time interval, a high-throughput transfer process of the solid film can be achieved. Therefore, when the above-mentioned high-energy laser transfer method is applied to a thick solid film, the stable transfer of the solid film can be ensured, while the transfer quality can be guaranteed. Furthermore, due to the effective use of thick solid films, the manufacturing difficulty and cost of the prior art due to the use of a thin solid donor film can be reduced, which greatly solves the shortcomings of the prior art.
[0051] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0052] Example 1
[0053] A. preparing a transfer film, wherein the transfer film comprises a transparent substrate and a solid film, wherein the solid film is attached to the inner surface of the transparent substrate;
[0054] B. applying a first transfer laser to the transfer film, allowing the first transfer laser to sequentially pass through the outer surface and the inner surface of the transparent substrate and irradiate the solid film to form a melted area;
[0055] C. After a preset time interval, a second transfer laser is applied to the transfer film, so that the second transfer laser sequentially passes through the outer surface and the inner surface of the transparent substrate and irradiates the melted area of the solid film.
[0056] In step A, the transparent substrate is 1 mm thick fused quartz glass, and a metal copper film with a thickness of 10 μm is prepared on the inner surface of the transparent substrate by a magnetron sputtering composite electroplating method.
[0057] In step B, the first transfer laser uses a continuous laser with an average power of 80W and a wavelength of 532nm. After focusing, the spot size of the first transfer laser when it reaches the solid film is 25μm, and the peak power density is 16.3MW / cm 2 .
[0058] In step C, since the thermal diffusivity of copper is 1.17 cm 2 / s, so for a copper film with a thickness of 10μm, b 2 / c=855ns, therefore, the preset time interval a in this embodiment is 4600ns. In addition, the second transfer laser uses nanosecond pulse laser with a wavelength of 532nm, a single pulse energy of 1μJ, and a pulse width of 1.2ns. After focusing, the spot size of the second transfer laser reaching the melting area of the solid film is 25μm, and the peak power density is 340MW / cm 2 .
[0059] When the first transfer laser irradiates the copper film, the solid-liquid region of the copper film evolves as follows Figure 2 As shown in the figure, after the copper film is irradiated by the first transfer laser, the material in the laser action area begins to melt. With the continuous input of laser energy, the melting area continues to expand in the vertical direction, and the molten pool continues to deepen. At 4600ns, the depth of the molten pool reaches 10μm, at which time the copper film is completely melted.
[0060] The maximum temperature evolution of the copper film over time from the start of the first transfer laser to the end of the second transfer laser is shown in the figure Figure 3 As shown. During the first transfer laser action, due to its low peak power, the highest temperature in the metal copper film is always lower than the vaporization temperature of metal copper (2840K). At this time, the physical phenomenon occurring inside the metal copper film is mainly due to the thermal diffusion effect, and it does not have a surface driving effect dominated by vaporization force. When the time reaches 4600ns and the second transfer laser begins to act, due to its extremely high peak power, the highest temperature in the metal copper film quickly exceeds the vaporization temperature of metal copper. At this time, the upper surface of the molten pool vaporizes violently, producing a strong driving effect, squeezing the melted area of the film downward. In view of the good match between the penetration depth and the vaporization time at this time, the film has a stable instantaneous vaporization driving force when it is fully melted, and finally a stable and high-throughput transfer effect can be formed.
[0061] Example 2
[0062] A. preparing a transfer film, wherein the transfer film comprises a transparent substrate and a solid film, wherein the solid film is attached to the inner surface of the transparent substrate;
[0063] B. applying a first transfer laser to the transfer film, allowing the first transfer laser to sequentially pass through the outer surface and the inner surface of the transparent substrate and irradiate the solid film to form a melted area;
[0064] C. After a preset time interval, a second transfer laser is applied to the transfer film, so that the second transfer laser sequentially passes through the outer surface and the inner surface of the transparent substrate and irradiates the melted area of the solid film.
[0065] In step A, the transparent substrate is 1 mm thick fused quartz glass, and a metal copper film with a thickness of 5 μm is prepared on the inner surface of the transparent substrate by electron beam evaporation process.
[0066] In step B, the first transfer laser uses a pulse laser with a pulse width of 1 μs and a wavelength of 532 nm. After focusing, the spot size of the first transfer laser when it reaches the solid film is 25 μm, the single pulse energy is 65 μJ, and the peak power density is 26.5 MW / cm 2 .
[0067] In step C, since the thermal diffusivity of copper is 1.17 cm 2 / s, so for a copper film with a thickness of 5μm, b 2 / c=214ns, therefore, the preset time interval a in this embodiment is 2000ns. In addition, the second transfer laser uses nanosecond pulse laser with a wavelength of 355nm, a single pulse energy of 2μJ, and a pulse width of 1.5ns. After focusing, the spot size of the second transfer laser reaching the melting area of the solid film is 25μm, and the peak power density is 543MW / cm 2 .
[0068] After the metal copper film is irradiated by the first transfer laser, the material in the laser action area begins to melt. With the continuous input of laser energy, the melting area continues to expand in the vertical direction, and the molten pool continues to deepen. At 2000ns, the metal copper film is completely melted.
[0069] The maximum temperature evolution of the copper film over time from the start of the first transfer laser to the end of the second transfer laser is shown in the figure Figure 4 As shown. During the first transfer laser action, due to its low peak power, the highest temperature in the metal copper film is always lower than the vaporization temperature of metal copper (2840K). At this time, the physical phenomenon occurring inside the metal copper film is mainly due to the thermal diffusion effect, and it does not have a surface driving effect dominated by vaporization force. When the time reaches 2000ns, the second transfer laser begins to act. Due to its extremely high peak power, the highest temperature in the metal copper film quickly exceeds the vaporization temperature of metal copper. At this time, the upper surface of the molten pool vaporizes violently, producing a strong driving effect, squeezing the melted area of the film downward. In view of the good match between the penetration depth and the vaporization time at this time, the film has a stable instantaneous vaporization driving force when it is fully melted, and finally a stable and high-throughput transfer effect can be formed.
[0070] Example 3
[0071] A. preparing a transfer film, wherein the transfer film comprises a transparent substrate and a solid film, wherein the solid film is attached to the inner surface of the transparent substrate;
[0072] B. applying a first transfer laser to the transfer film, allowing the first transfer laser to sequentially pass through the outer surface and the inner surface of the transparent substrate and irradiate the solid film to form a melted area;
[0073] C. After a preset time interval, a second transfer laser is applied to the transfer film, so that the second transfer laser sequentially passes through the outer surface and the inner surface of the transparent substrate and irradiates the melted area of the solid film.
[0074] In step A, the transparent substrate is 1 mm thick fused quartz glass, and a metal tin film with a thickness of 5 μm is prepared on the inner surface of the transparent substrate by a magnetron sputtering process.
[0075] In step B, the first transfer laser uses a continuous laser with an average power of 30W and a wavelength of 532nm. After focusing, the spot size of the first transfer laser when it reaches the solid film is 25μm, and the peak power density is 6.1MW / cm 2 .
[0076] In step C, since the thermal diffusivity of tin is 0.40 cm 2 / s, so for a tin film with a thickness of 5μm, b 2 / c=625ns, therefore, the preset time interval a in this embodiment is 180ns. In addition, the second transfer laser uses nanosecond pulse laser with a wavelength of 532nm, a single pulse energy of 0.5μJ, and a pulse width of 1.5ns. After focusing, the spot size of the second transfer laser reaching the melting area of the solid film is 25μm, and the peak power density is 136MW / cm 2 .
[0077] When the first transfer laser irradiates the metal tin film, the solid-liquid region of the metal tin film evolves as follows Figure 5 As shown in the figure, after the metal tin film is irradiated by the first transfer laser, the material in the laser action area begins to melt. With the continuous input of laser energy, the melting area continues to expand in the vertical direction, and the molten pool continues to deepen. At 180ns, the depth of the molten pool reaches 4μm, at which time the metal tin film is in a state of mostly melted through.
[0078] The evolution of the maximum temperature in the metal tin film over time from the start of the first transfer laser to the end of the second transfer laser is shown in the figure Figure 6As shown. During the first transfer laser action, due to its low peak power, the highest temperature in the metal tin film is always lower than the vaporization temperature of metal tin (2875K). At this time, the physical phenomenon occurring inside the metal tin film is mainly due to the thermal diffusion effect, and it does not have a surface driving effect dominated by vaporization force. When the time reaches 180ns and the second transfer laser begins to act, due to its extremely high peak power, the highest temperature in the metal tin film quickly exceeds the vaporization temperature of metal tin. At this time, the upper surface of the molten pool vaporizes violently, producing a strong driving effect, squeezing the melted area of the film downward. In view of the good match between the penetration depth and the vaporization time at this time, the film has a stable instantaneous vaporization driving force when it is fully melted, and finally a stable and high-throughput transfer effect can be formed.
[0079] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A high-throughput laser transfer method for solid-state thin films, characterized in that: The following steps are involved: A. preparing a transfer film, wherein the transfer film comprises a transparent substrate and a solid film, wherein the solid film is attached to the inner surface of the transparent substrate; B. applying a first transfer laser to the transfer film, allowing the first transfer laser to sequentially pass through the outer surface and the inner surface of the transparent substrate and irradiate the solid film to form a melted area; C. After a preset time interval, a second transfer laser is applied to the transfer film, so that the second transfer laser sequentially passes through the outer surface and the inner surface of the transparent substrate and irradiates the melted area of the solid film; In step B, the peak power density of the first transfer laser when it reaches the solid film is ≤50MW / cm 2 ; In step C, the peak power density of the second transfer laser when it reaches the solid film is ≥100MW / cm 2 .
2. The high-throughput laser transfer method of a solid-state thin film according to claim 1, characterized in that: In step C, the preset time interval is a, the unit is s, and a satisfies: 0.1*(b 2 / c)≤a≤10*(b 2 / c); Wherein, b is the thickness of the solid film, in m; c is the thermal diffusivity of the material of the solid film, in m 2 / s.
3. The high-throughput laser transfer method of solid-state thin film according to claim 1, characterized in that: In step B, the first transfer laser is a continuous laser.
4. The high-throughput laser transfer method of a solid-state thin film according to claim 1, characterized in that: In step B, the first transfer laser is a pulse laser, and the pulse width of the first transfer laser is ≥1 μs.
5. The high-throughput laser transfer method for solid-state thin films according to claim 1, characterized in that: In step C, the second transfer laser is a pulse laser, and the pulse width of the second transfer laser is 0.1-100 ns.
6. The high-throughput laser transfer method for solid-state thin films according to claim 1, characterized in that: The thickness of the solid film is ≥5 μm.
Citation Information
Patent Citations
Method for repairing printed circuit trace and equipment
CN104797087A
Printing method using two lasers
CN107852818A
Method of manufacturing oxide dot pattern, and the oxide dot pattern
JP2014172087A
Direct-write laser transfer and processing
US7001467B2
Semiconductor thin film manufacturing method and semiconductor thin film manufacturing apparatus
WO2006075569A1
Cited By
High-throughput transfer printing method for solid film
CN122078083A